Photography in the Arctic Archipelago during the First International Polar Year, 1882–1883 - Fjellestad, Marthe (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2022)
August 1, 1882, marked the start of the First International Polar Year, IPY-1, when natural science researchers conducted observations from stations positioned across the Arctic and Antarctic. IPY-1 took place as photography increasingly played a part in Arctic exploration, and with the polar year came an opportunity to further photographic experimentation and the emerging photographic documentation of Arctic lands. Here, I do a first review of the use of photography during three IPY-1 expeditions to the Arctic Archipelago, arguing that focused and strategic planning was key to the development of Arctic photography from an almost incidental expedition activity to a ubiquitous pursuit for images.